A research report on identifying factors and environmental change to disease outbreak and impact on household economy in Jajarkot district in Nepal . - Paudel,Uttam (2018)
SUMMARY: Nepal is one of the most vulnerable countries due to environmental damage including climate change and household characteristics, and also the household daily behaviors including economic aspects. A clear picture of association between environmental change and sudden outbreak of diseases may help to identify the total cost incurred at present and can predict the future consequences possibly concocted by exogenous natural hazards. The recent epidemiology information of Jajarkot indicates that there occurs continuous outbreaks. Other districts have similar socio economic characteristics such as remoteness, lack of access to facility, education, HDI, and equal health facilities among other but why Jajarkot is facing diseases outbreak every year. This is an unreached area of the researcher but an urgent information required to save a gigantic societal cost and for having economically prosperous society. To fulfill this objective this research, multiple logistic regression is employed among environmental, socioeconomic and household behavioral variables to identify the results. Moreover, health inaction cost and natural hazard cost are also estimated. Result divulges that decreasing trees and drying spout are significant determinants in the study areas which cover almost all the aspects of environment. Moreover, sporadic rain, thunderstorm, cold waves, winter rain are also potential variables to increase the strength of explanatory significant variables but insignificant to reveal direct association with disease occurrence. Household Size, education, hand washing habit, cooking fuel, boiled drinking water, use of pesticide, place of kitchen waste collection are also significant in the category of socioeconomic and household behavioral potential factors to influence the high prevalence of disease. Average total household curative cost and average household preventive cost is found as Rs. 80383 and Rs 85999 within five year time period.Cost induced by climatic hazards has reached up to Rs. 244724 in average for few affected households. Therefore, Nepal government and other global cohort has to urgently lunch the program addressing the major factors influencing in the diseases prevalence in Jajarkot as soon as possible to protect the lives and further impoverishment of the locals of the district.